ABOUT THE HISTORY OF THE RUSSIAN INVADER'S ENTRY TO TERMIZ - Raimov Mamasoat Safar ugli (Journal of Learning on History and Social Sciences, 2024)
The article covers the study of the past of Termiz and the historiography of scientific literature about it, which includes a number of aspects that can be a separate topic for each scientific research